(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Physico-substance Analysis of blessed stream ganga of Varanasi city (U.P.), India in month of February, 2016. Water tests were gathered from seven unique destinations in particular (S1)- Gangamahal Ghat, (S2)- Chedilal Ghat, (S3)- Jain Ghat, (S4)- Prabhu Ghat, (S5)- Niranjini Ghat, (S6)- Mahanirvini Ghat and (S7)- Shivala Ghat. The scope of perceptions are as under pH of stream water ranges between 7.0 to 7.8, Electrical conductivity from 0.45 to 0.58 dSm-1, Cl from 1.50-4.0 mg L - 1, Ca+Mg from 23.50-27.50 mg L - 1, CO3+HCO3 from 2.80-4.20 mg L - 1, SO4 from 16.00-36.00 mg L - 1, Na from 0.40-0.90 mg L - 1, K from 1.10-1.40 mg L - 1, TS from 800-1600 mg L - 1, DO from 5.30-7.30 mg L - 1, COD from 15.20-24.00 mg L - 1, NO3 from 20.23 - 24.24 mg L - 1 and SAR from 0.14-2.50. Ordinary observing of Ganga waterway water quality is important to have a keep an eye on surface water quality for human life and to keep up a decent aesthetical estimation of strict.